Royal inviolability and its limits in the Spanish legal system - Jon (Journal of the Basque Parliament, 2022)
This article addresses the potential for conflict between royal inviolability and the principles which characterise a social and democratic State, subject to the rule of law, as is the Kingdom of Spain, and aims at exploring the limits of the king’s inviolability both from the perspective of interpretation of the current legislation and from the perspective of a reform proposal. It is assumed as a hypothesis that “inviolability” is not —or should not be— equivalent to “impunity” in a social and democratic state, subject to the rule of law, which advocates equality and justice, among others, as the highest values of its legal order. After clarifying the concepts of inviolability, non-accountability and countersignature, the article addresses the different doctrinal stances on the delimitation of this royal prerogative in terms of time, in terms of material scope, and vis-à-vis the legislative power. Eventually, a modest reform proposal is drafted.